2011
DOI: 10.1007/s12033-011-9423-5
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Varietal Genetic Variability in Malvasia Cultivars

Abstract: The DNA molecular analyses together with ampelography, ampelometry, and biochemistry are essential for grapevine identification and investigation of genetic differences among the Vitis vinifera L. cultivars and clones. Ten Malvasia cultivars (i.e., Istrian Malvasia; M. delle Lipari; M. bianca di Candia; M. di Candia Aromatica; M. del Lazio; M. bianca lunga, also known as Malvasia del Chianti; M. nera di Brindisi/Lecce; M. di Casorzo; M. di Schierano, and M. nera di Bolzano) were analyzed using molecular approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Many studies have reported the intra-varietal genetic variability [4143]. However, only the genotypic variations among cultivated bromeliads were investigated, with the genetic variability within asexual clones of genotypes neglected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the intra-varietal genetic variability [4143]. However, only the genotypic variations among cultivated bromeliads were investigated, with the genetic variability within asexual clones of genotypes neglected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Minor genetic variation was observed among the different "Rocha" clones, which could be due to somatic mutations related to grafting [35] or, in some cases, the results of hybridization with unknown pear plants. Previously, a great variability and heterogeneity was referred among Malvasia grapevine clones that were cultivated in different geographic areas [36,37]. Clonal variation has also been reported within ancient Portuguese grapevine varieties [38].…”
Section: Genetic Relationships Among Pear Genotypesmentioning
confidence: 93%
“…Amplified fragment length polymorphisms analysis has proven useful for discriminating among grapevine cultivars [46] but the method has the disadvantage of generating a complex series of bands that may be difficult to interpret and standardize. However, this method and modified versions have shown to be powerful to investigate polymorphisms among clones and assess inter-and intracultivar diversity [47][48][49][50].…”
Section: Dna-based Methodsmentioning
confidence: 99%
“…A set of six specific dinucleotide STRs already widely used (VVMD5, VVMD7, VVDM27, VVS2, VrZAG62, and VrZAG79) was agreed upon by the members for future analyses (Table 1). After converting raw data into normalized data through a coding method, the authors reported discrepancies of the results among the members: genotyping errors, [17,20,23,24,28,33,35,41,49,50,65,[69][70][71][72][74][75][76][77][78][79][80][81][82][83][84][85][86]89,91,92] SsrVrZAG79 [17,20,23,24,28,33,35,41,49,50,65,[69][70][71][72][74][75]…”
Section: Commonly Used Strs For Grapevine Genotypingmentioning
confidence: 99%